Wound Dressings: An Advanced Multifunctional Hydrogel‐Based Dressing for Wound Monitoring and Drug Delivery (Adv. Healthcare Mater. 19/2017). Issue 19 (11th October 2017) - Mirani, Bahram; Pagan, Erik; Currie, Barbara; Siddiqui, Mohammad Ali; Hosseinzadeh, Reihaneh; Mostafalu, Pooria; Zhang, Yu Shrike; Ghahary, Aziz; Akbari, Mohsen
Abstract : Wound management is a major global challenge and poses a significant financial burden to the healthcare system. In article1700718, Mohsen Akbari and co‐workers develop an advanced multifunctional dressing (GelDerm) capable of colorimetric measurement of pH, an indicator of bacterial infection, and release of antibiotic agents at the wound site. GelDerm makes wound care easier and less painful to the patient, and more cost‐effective for the healthcare system.